Evaluation of damage caused by caterpilar Erinnyis ello in hevea stock nursery - Filho, Pedro Celestino; Rossetti, Adroaldo Guimarães; Neto, Olinto Gomes da Rocha; Magalhães, Francisco Exgidas Leite (Pesquisa Agropecuaria Brasileira, 2014)
The damage caused by the caterpilar of Erinnyis ello (Linné, 1758) in stock nursery at different levels of infestation (0, 4, 8 and 16 caterpilar/10 plants) was evaluated. For evaluation, the plants were protected by cages made from nylon screen and wood. It was observed that the damage was significant only at 16 caterpilar/10 plants or more. At this level, only 52.2% of the plants reached good grating condition when compared to the control.
Keywords: rubber tree; cages; levels of infestation; larvae